ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS 5 SEKOLAH DASAR PADA MATERI RASIO DAN DIAGRAM - CIPTA, KAVITA HATARU; Bela Anggraini, Salsa; Tasya, Nikmatul; Ummam, Fatikhul; Puspita Sari, Melda; Hemalia, Hemalia; Rahayu, Ratri (AL KHAWARIZMI: Jurnal Pendidikan Matematika, 2025)
This research aims to analyze the mathematical reasoning abilities of grade V students at SDN 5 Mejobo on ratio and diagram material. The method used in this research is a descriptive method with a qualitative approach. The subjects of this research were grade V students. Data was collected through mathematical reasoning tests, interviews and observations. The research results show that students' mathematical reasoning abilities in understanding the concept of ratios and diagrams are still at a medium level. Some students are able to apply the concept of ratios in various problem contexts, but most students have difficulty interpreting and making diagrams correctly. Things that influence this reasoning ability include a lack of understanding of basic concepts, a lack of practice on varied questions, and a lack of use of learning media that supports understanding the concepts of ratios and diagrams. Based on this research, it is recommended that teachers increase the use of interactive learning media and provide more varied practice questions to improve students' mathematical reasoning abilities.